Some psychological factors that affect emotional intelligence of Lithuanian high school students - Antinienė, Dalia; Lekavičienė, Rosita (Social Welfare: Interdisciplinary Approach, 2019)
This study explores relationships among high school students’ emotional intelligence, subjective health status, depressiveness, anxiety and psychological well-being. Participants were 16–19 years old students (n=371) from high schools in various regions of Lithuania. The results suggested that total emotional intelligence positively correlates with psychological well-being and negatively correlates with subjective health status, depressiveness, and anxiety subscales.
Keywords: anxiety; depressiveness; emotional intelligence; psychological well-being; subjective health status